2021
DOI: 10.1007/s12144-021-02185-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio-emotional strengths against psychopathology and suicidal ideation in fear of COVID-19

Abstract: Coronavirus disease (COVID-19) has caused a global health crisis. It also leads to different types of psychosocial problems in society as a result of preventive health measures and the disease itself. Among others, psychopathological symptoms and suicide behaviors have increased. The PsicorecurSOS COVID-19 online protocol was designed. At baseline, 1020 Spanish adults were assessed, during confinement, for sociodemographics, fear of COVID-19, anxious-depressive symptoms, covitality, and suicidal ideation. Reli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The context in which the individual lives seems to play a key role in the acquisition and development of SECs [ 45 ]. According to Soto-Sanz et al [ 46 ], individuals with more SECs are more protected against the impact of disasters. Based on this premise, it was possible to verify in a sample of Portuguese individuals that they show a median perception of social and emotional competencies; they are high in self-awareness, which is followed by social awareness and pro-social behavior, self-management and motivation, and they are low in the decision-making domain.…”
Section: Discussionmentioning
confidence: 99%
“…The context in which the individual lives seems to play a key role in the acquisition and development of SECs [ 45 ]. According to Soto-Sanz et al [ 46 ], individuals with more SECs are more protected against the impact of disasters. Based on this premise, it was possible to verify in a sample of Portuguese individuals that they show a median perception of social and emotional competencies; they are high in self-awareness, which is followed by social awareness and pro-social behavior, self-management and motivation, and they are low in the decision-making domain.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the present authors’ knowledge, the contemporary evidence has supported the associations between fear of COVID-19, insomnia, and suicidal ideation during the COVID-19 pandemic [ 16 , 26 ]. However, there is a lack of empirical evidence regarding how generalized trust is associated with fear of COVID-19, insomnia, and suicidal ideation during the COVID-19 pandemic period.…”
Section: Introductionmentioning
confidence: 90%
“…In another study, fear of COVID-19 was significantly associated with suicidal ideation among 1013 English-speaking Americans [ 16 ]. Similarly, it was found that fear of COVID-19, together with psychological distress, explained 27% of the risk regarding suicidal ideation among 595 Spanish adults [ 26 ]. The relationship between fear and suicidal ideation has also been found in another coronavirus (i.e., SARS) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several tourism marketing scholars have explored the moderating role of fear of COVID-19 in the relationship between attitudes (satisfaction, engagement) and behavior Rather, 2021;Akhrani et al, 2022). However, most studies using fear of COVID-19 as a moderating variable have also focused on the mental health domain (Gasparro et al, 2020;Dymecka et al, 2021;Soto-Sanz et al, 2021). This study builds on the fear of COVID-19 definition by Ahorsu et al (2020).…”
Section: The Moderating Role Of Fear Of Covid-19mentioning
confidence: 99%